REFORMULASI PENGATURAN SANKSI PIDANA BAGI PELAKU USAHA YANG MELAKUKAN PENIMBUNAN BAHAN PANGAN PADA SAAT TERJADI KELANGKAAN BARANG - Muhammad Fadhil Muzzammil; Davit Rahmadan; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The act of hoarding food is a criminal act that has an economic motive, so it is a formof crime, because it is detrimental to society and the State. Business actors who commit theseacts will be subject to penalties and sanctions in accordance with Law Number 7 of 2014concerning Trade and Law Number 18 of 2012 concerning Food. In the regulation of sanctionsin this law, there are no specific minimum sanctions regulations so that in their decisionsjudges can impose criminal sanctions that are too light. Therefore, the aim of this thesisresearch is first, to determine the need to reformulate the regulation of criminal sanctionsagainst individual business actors who hoard food when there is a shortage of goods in thefuture. Second, to formulate relevant forms of criminal sanctions against business actors whohoard food when there is a shortage of goods in the future.This type of research can be classified into a type of normative legal research. In thistype of legal research, law is often conceptualized as what is written in statutory regulationsor laws. Therefore, the first source of data is only secondary data, which consists of primarylegal material, secondary legal material and tertiary data.From the results of this research, the first result was obtained, namely the need toreformulate the regulation of sanctions against perpetrators of criminal acts of food hoardingin Article 107 of Law Number 7 of 2014 concerning Trade and Article 133 of Law Number 18of 2012 concerning Food. These two articles are not listed. special minimum criminal threat,then in his decision the judge does not have a reference in giving a decision so that theperpetrator of a criminal act can be given a sanction that is too light. Second, regulation ofrelevant criminal sanctions for business actors who commit criminal acts of food hoardingwith efforts to reform Indonesian criminal law, namely by including special minimum criminalsanctions in the form of imprisonment for a minimum of 1 (one) year.Keywords: Reformulation, Business Actors, Food Hoarding.